Optimising small-scale electronic commerce supply chain operations: a dynamic cost-sharing contract approach - Nripendra Rana (Annals of Operations Research, 2022)
For small-scale electronic commerce supply chains, designing effective strategies to improve operational effectiveness, market share and long-term survival are essential aspects. However, researchers have given less attention in addressing these issues. This study proposes a dynamic cost-sharing contract for an e-tailer supply chain to address the issues of asymmetric information, long-term integration, and ineffective costs. We include consistency constraints to obtain stable incentives over time and eliminate the need for re-negotiation. The findings emphasise that the dynamic contract significantly reduces the overall supply chain costs. The consistency constraints guarantee high incentives, thus assuring the players remain in the total contract period and enable long-term integration.